The impact of anti-infective therapy on patients undergoing warfarin treatment - Linlin Fu; Huimin Yao; Wei Xu; Li Li; Baoyan Wang (Journal of Infection in Developing Countries)
Introduction: The combination of antibiotics and warfarin is used frequently in clinical practice. However, the impact of this combination on the anticoagulant efficacy of warfarin remains uncertain, posing challenges to clinical decision-making. This study aimed to evaluate the influence of various antibiotics on the international normalized ratio (INR) values in hospitalized patients who were concurrently administered warfarin.